Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1007/bf01744504
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary blood flow profiles with reduced right ventricular function in lambs

Abstract: The determinants of right ventricular (RV) performance with damaged RV free wall, such as occurs with RV infarction, are still unclear. Using 20-MHz Doppler ultrasound equipment, we investigated the changes in pulmonary blood flow velocity profiles before and after ligation of the right coronary artery. RV dp/dt, stroke volume, RV stroke work, aortic pressure and cardiac output decreased and central venous pressure rose after the ligation. The RV stroke work-end-diastolic pressure relationship indicated impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…10,12 Recently, experimental studies have reported the potential usefulness of the pulmonary flow patterns in the evaluation of right ventricular performance in the experimental RV infarction. 13 The goal of the study was to assess RV systolic performance in patients with inferior MI by means of Doppler echocardiography of pulmonary flow and to correlate them with hemodynamic findings.…”
Section: Introduction 'mentioning
confidence: 99%
“…10,12 Recently, experimental studies have reported the potential usefulness of the pulmonary flow patterns in the evaluation of right ventricular performance in the experimental RV infarction. 13 The goal of the study was to assess RV systolic performance in patients with inferior MI by means of Doppler echocardiography of pulmonary flow and to correlate them with hemodynamic findings.…”
Section: Introduction 'mentioning
confidence: 99%